From Hope to Despair, and Back: Being the Wife of a Patient in a Persistent Vegetative State. (February 2013) - Hamama-Raz, Yaira; Zabari, Yonit; Buchbinder, Eli
In this study we examined the meaning of being the wife of a vegetative patient over time. The research was based on semistructured interviews with 12 wives of husbands who were diagnosed with persistent vegetative state between 1 year 2 months and 10 years prior to the interview. We found that there were two contradicting forces common to all of the wives across time. First, there was a process of finding significance in the situation based on acceptance of the husband's condition and focusing on positive emotions and values such as love, commitment, and loyalty. Second, the wives described an increase in negative emotions such as sadness, pain, loneliness, loss, and grief. These findings are discussed in the context of research and theoretical literature about coping processes and the meaning of caring for patients in a persistent vegetative state.